2022
DOI: 10.1111/jphd.12528
|View full text |Cite
|
Sign up to set email alerts
|

Variations in temporal trends in non‐traumatic dental condition related emergencies

Abstract: Objective The objective of the study was to investigate temporal trends in non‐traumatic dental condition (NTDC) related emergency visits at Emergency Department (ED), urgent care (UC), and at a Federally Qualified Health Center (FQHC) that providing dental services to a mid‐sized rural community. Methods Temporal trends over a 9‐year period (2008–2016) in NTDC rates at ED, UC, FQHC and in a region around the FQHC were determined. Statistically significant changes (α = 0.05) in the proportion of NTDC visits be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“… 13 , 14 This treatment regimen is largely palliative in nature and occurs in settings that lack dental specialists and the infrastructure needed to provide definitive care (ie, extractions, root canal treatment, pulp therapy, abscess drainage, sedation). 15 , 16 As a result, opioid prescription utility and concurrent drug dependence may have affected individuals seeking pain relief for dental conditions. Prior research concluded that the prescribing of opioids for NTDC patients during 2007 to 2010 increased significantly over time and was higher than opioid prescribing among non-NTDC visits, based on the National Hospital Ambulatory Medical Care Survey.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 This treatment regimen is largely palliative in nature and occurs in settings that lack dental specialists and the infrastructure needed to provide definitive care (ie, extractions, root canal treatment, pulp therapy, abscess drainage, sedation). 15 , 16 As a result, opioid prescription utility and concurrent drug dependence may have affected individuals seeking pain relief for dental conditions. Prior research concluded that the prescribing of opioids for NTDC patients during 2007 to 2010 increased significantly over time and was higher than opioid prescribing among non-NTDC visits, based on the National Hospital Ambulatory Medical Care Survey.…”
Section: Introductionmentioning
confidence: 99%